"Every child needs an adult apart from their family that they can talk to": An investigation into school staff perceptions of the provision of external psychological services. (22nd March 2020) - Freeman, Nerelie C.; Lunardi, Leanne
Abstract: Objective: Schools are ideally placed to provide early identification and intervention for children and adolescents with mental health issues, traditionally with support from Government‐employed school psychologists. This model of service provision has recently undergone a change with schools utilising external psychological providers. No research has previously been undertaken in Australia regarding this change. The present study aimed to gain feedback from staff regarding their perceptions of external psychological services provided in schools. Method: Ten staff in wellbeing roles aged 31–63 years from nine Government schools across Melbourne, Victoria completed a semi‐structured interview. Results: Staff reported positive perceptions of external psychological providers related to improved access to much‐needed therapeutic services, but voiced concerns over a lack of formal contractual agreements and access to files post‐treatment. Despite the need for their services, staff still preferred Government‐employed school psychologists. Conclusions: Findings implicate an ongoing need to meet an increasing demand for therapeutic supports to children and adolescents within school settings. Issues such as communication and access to files appear to compromise ethical practice, which potentially hinder continuity of care once the external provider ceases working with a young person. Better communication between all concerned parties may help mitigate this issue.